Seizure outcome and prognostic factors for surgical management of hypothalamic hamartomas in children. (February 2020) - Ferrand-Sorbets, Sarah; Fohlen, Martine; Delalande, Olivier; Zuber, Kevin; Bulteau, Christine; Levy, Mikael; Chamard, Pauline; Taussig, Delphine; Dorison, Nathalie; Bekaert, Olivier; Tisdall, Martin; Chipaux, Mathilde; et al.
Highlights: Largest pediatric series with a median follow-up of 37 months (up to 77 months). Time from HH diagnosis to surgery is a predictive factor for seizure outcome. Endoscopic disconnection remains effective technique, for all seizures types. Endoscopic disconnection has no delayed efficiency. Abstract: Purpose: Hypothalamic hamartomas (HH) are rare benign lesions frequently associated with gelastic seizures early in life. Epilepsy can progress to multiple seizure types with cognitive impairment and behavioural disturbance, leading in some cases to epileptic encephalopathy. Methods: We reviewed a retrospective series of 112 children treated in a single center, between 1998 and 2017. Results: According to Delalande's HH classification, type1 was found in 2 patients, type 2 in 67, type 3 in 31, and type 4 in 12 patients. Stereotactic endoscopic disconnection was performed in 92 % of the procedures. Median age at diagnosis was 40 months and 7.6 years at surgery. Median time between diagnosis and surgery was 31 months and median follow up 4.1 years. For all HH types, 77.6 % of the patients had a favourable outcome (Engel I + II outcome score) with 57.1 % seizure-free (Engel I). The best outcome was obtained in patients with type 2 HH, (68.7 % Engel I and 85.1 % Engel I + II). The overall complication rate was 8.3 %, which is in line with previous series. Patients with isolated gelastic seizures had a better outcome (Engel I + II in 90 %), as compared to those with other seizure types (p = 0.07). A short delay between hamartoma diagnosis and surgery was a statistically significant factor for a good outcome (p = 0.03). Conclusion: Patients with HH and drug-resistant epilepsy should be early identified in order to propose surgical treatment without delay. Endoscopic disconnection is a safe and efficacious surgical option with good seizure outcome and immediate treatment results.